Analysis of The Open Reading Frame (ORF) 29-TrnC (GCA) Sequence to Detect Indica and Japonica Sub Species on Upland Rice of Situ Bagendit and Inbred Rice of Ciherang - Rohma Istiana; Hermin Pancasakti Kusumaningrum; Rejeki Siti Ferniah (Biosaintifika: Journal of Biology & Biology Education, 2018)
The identification and the characterization of genetic diversity of rice was the first step in the rice plant breeding program. This study aimed to detect indica or japonica sub-species on upland rice Situ Bagendit and inbred rice Ciherang using molecular markers ORF 29-TrnC (GCA) on the chloroplast genome. Rice was included to the indica sub-species if the 32 bp insertion on ORF 29-TrnC (GCA) sequence was found, on the contrary, if the deletion 32 bp on ORF 29-TrnC (GCA) was found then it was included to the japonica sub-species. DNA isolation was examined from the leaves of the rice plants, and then it tested quantitatively to determine the transparency and DNA concentration from the isolation results. PCR amplification was performed using a pair of primers CP2 and it was followed by agarose gel electrophoresis. The visualization of the DNA bands used the gel documentation. Sequencing of PCR products produced a long base 390 bp in Situ Bagendit rice and 390 bp in Ciherang rice. Analysis of the sequences showed that the insertions occurred throughout the 32 bp in Situ Bagendit rice and the insertions occurred throughout the 32 bp in Ciherang rice. The results showed that upland rice Situ Bagendit and inbred rice Ciherang were included in the indica sub-species. The knowledge of variety of genetics of rice can be used as bio-information in the plant breeding program. Further, the knowledge can be used to protect in genetic power source, the selection and the composing of superior varieties of rice which is tolerant with kinds of biotic and abiotic factor.